1997
DOI: 10.1104/pp.115.3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression of Caffeoyl-Coenzyme A 3-O-Methyltransferase Proposed for the Induced Resistance Response of Vitis vinifera L

Abstract: Cell-suspension cultures of Vitis vinifera L. cv Pinot Noir accumulated resveratrol upon fungal elicitation, and the activity of S-adenosyl-i-methi0nine:trans-caffeoyl-coenzyme A 3-O-methyltransferase (CCoAOMT), yielding feruloyl-COA, increased to a transient maximum at 12 to 15 h. CCoAOMT cDNA was cloned from the elicited cells and was shown to encode a polypeptide highly homologous to CCoAOMTs from cells of Petroselinum species or Zinnia species. The expression of the cDNA i n Escherichia coli revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 46 publications
(52 reference statements)
3
32
1
Order By: Relevance
“…This strongly suggests that the PFOMT may indeed be involved in the methylation of these compounds. Similar responses to biotic or abiotic stresses have been observed on the transcript level for several other CCoAOMT-like genes (36,44,46,47).…”
Section: Substrate Specificities Of Other Ccoaomt-like Proteins-supporting
confidence: 50%
“…This strongly suggests that the PFOMT may indeed be involved in the methylation of these compounds. Similar responses to biotic or abiotic stresses have been observed on the transcript level for several other CCoAOMT-like genes (36,44,46,47).…”
Section: Substrate Specificities Of Other Ccoaomt-like Proteins-supporting
confidence: 50%
“…However, some type 2 OMTs are also active with flavonoids and/or phenylpropanoid conjugates (Ibdah et al, 2003;Kim et al, 2006;Lee et al, 2008). The candidate AOMT presented 56% and 54% identity with PFOMT from M. crystallinum (Ibdah et al, 2003) and caffeoylCoA-OMT (CCoA-OMT) from grapevine (Busam et al, 1997), respectively (Fig. 1A).…”
Section: Isolation Of a Candidate Aomt Cdna From Grapevinementioning
confidence: 99%
“…Substrate affinity analysis has revealed that CCoAOMT shows higher methylation rate with caffeoyl-CoA than 5-hydroxyferuloyl-CoA (Ye et al, 1994;Busam et al, 1997;Martz et al, 1998;Zhong et al, 2000). CCoAOMT is reported to exist in a multigene family that can be grouped into class I and II (Raes et al, 2003).…”
Section: Sl Pang Et Almentioning
confidence: 99%
“…It has been reported that this gene is encoded by one to two members in parsley (Grimmig and Matern, 1997), grapevine (Busam et al, 1997), alfalfa (Inoue et al, 1998) and aspen (Meng and Campbell, 1998), five to ten members in zinnia (Ye et al, 1994), and seven members in Arabidopsis (Raes et al, 2003). There are three classes of CCoAOMT in tobacco, and it was suggested that each class plays a role at different stages of lignification (Maury et al, 1999).…”
Section: Introductionmentioning
confidence: 99%